(untitled) (Itinera, 2019)
Having reached the apex of her fame in the 30s, Irène Némirovsky regained her popularity in 2004, when her posthumous novel French Suite was published, prompting the re-publication of all her works. Known as author of novels, Némirovsky would have liked to write exclusively for the cinema. She authored four plays which never became films. With Hollywood in her mind, three unsuccessful attempts and movies based on her works, Némirovsky wrote great literature thinking about the big screen. Key words: Némirovsky, literature, cinema, plays.